TRANSFORMASI PENDIDIKAN ISLAM - Mohammad Hendra (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
The Indonesian nation, where the majority of the population is Muslim, is the center of the largest concentration of Muslims in the world, definitely requires truly qualified Islamic educational institutions dedicated to the interests of the nation as a whole, so that Islamic insights are always related to Indonesian insights. and research objectives, research methods, and research findings or ideas. This research method is a literature review. The results of the research show that Islamic education wants to give birth to quality human beings who can be happier than their predecessors, by increasing their intellectual capacity, but not abandoning their spiritual model that lives in the culture of the nation and its people. Keywords: transformation, Islam Education, Quran